Concealing Messages at the Atomic‐Thin Level by Reaching the Limit of Writing. Issue 5 (27th October 2021) - Hou, Chao; Yang, Qirong; Guan, Jianxin; Deng, Jingwen; Xu, Zihan; Yu, Zhihao; Zheng, Junrong
Abstract: The evolution of writing system reflects the development of civilization. Using a single molecular layer of "ink" to record invisible messages on an atomic‐layered paper represents the ultimate thinness of classical writing system and steganography. A stable and convenient atomic‐thin information steganography under ambient conditions is realized using a monolayer of water as "ink, " an atomic layer of MoS2 as paper, and a laser as the pen. Physically adsorbed monolayered water molecules produce p‐type doping to the monolayer MoS2, leading to its photoluminescence (PL) enhancement. Information is written using a laser to remove surface water with designed patterns and is read out by PL imaging. The information is transparent to visible light and can retain for at least one week until erased by a humidification treatment. The method reaches the thinnest limit of writing and achieves repeatable data storage, providing promising applications in steganography and high‐density storage at the atomic‐thin level. Abstract : Using a monolayer of water as "ink, " an atomic layer of MoS2 as paper, and a laser as the pen, concealing information at the atomic‐thin level is achieved under ambient conditions in a rewritable manner. The erasable and rewritable information is realized by modulating and imaging the photoluminescence of monolayer MoS2 with surface water reversible adsorption and desorption.